Stress, Social Support, and Sexual Adjustment in Married Female Patients with Breast Cancer in Korea - Jiyoung Kim; Miyoung Jang (Elsevier, 2020)
Objective: This study identified the level of stress, social support, and sexual adjustment in married women with breast cancer in Korea. Methods: This study used a subgroup analysis, prospective, cross-sectional, and descriptive correlation design. Data were obtained using the perceived stress scale, multidimensional scale of perceived social support, and sexual adjustment subscale of the Korean version of the psychosocial adjustment to illness scale. From May 2015 to April 2016, 272 married female patients who had been diagnosed with breast cancer were recruited at a university hospital in Korea. Data were analyzed using SPSS Win 21.0. Results: The mean score of stress level was 17.53 ± 4.13, social support was 5.37 ± 1.07, and sexual adjustment was 6.36 ± 3.29. A significant positive correlation emerged between sexual adjustment and stress (r = 0.161, P = 0.008). Significant negative correlations were observed among sexual adjustment and family support (r = -0.177, P = 0.003) and friends' support (r = -0.205, P = 0.001). Conclusions: The assessment of stress level and social support may be used in planning sexual-adjustment interventions appropriate for married female breast cancer patients in Korea.